2017
DOI: 10.1167/iovs.16-20485
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2 Blockade Promotes Survival of Corneal Transplants

Abstract: PurposeCorneal transplantation remains the last hope for vision restoration, and lymphangiogenesis (LG) is a primary mediator of transplant rejection. This study was to investigate the specific role of angiopoietin-2 (Ang-2) in transplantation-associated LG and graft rejection.MethodsOrthotopic corneal transplantation was performed between fully mismatched C57BL/6 (donor) and BALB/c (recipient) mice to assess the effects of Ang-2 blockade via neutralizing antibody. Grafts were evaluated in vivo by ophthalmic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The analysis was performed as previously reported. 21 24 For evaluation of central corneal thickness and peripheral anterior synechiae, an anterior-segment optical coherence tomography (OCT; Visante OCT MODEL 1000; Carl Zeiss Meditec, Dublin, CA, USA) was used. Quadrant-scans along four axes (0°–180°, 45°–225°, 90°–270°, and 135°–315°) were performed to ensure scanning through the central cornea and data along the 0° to 180° axis were used for analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was performed as previously reported. 21 24 For evaluation of central corneal thickness and peripheral anterior synechiae, an anterior-segment optical coherence tomography (OCT; Visante OCT MODEL 1000; Carl Zeiss Meditec, Dublin, CA, USA) was used. Quadrant-scans along four axes (0°–180°, 45°–225°, 90°–270°, and 135°–315°) were performed to ensure scanning through the central cornea and data along the 0° to 180° axis were used for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment was performed as described previously. 24 Briefly, whole-mount limbal tissues were harvested at day 7 post-procedure, fixed in 4% paraformaldehyde, and immunostained with primary rat-anti-mouse CD31 antibody (BD Pharmingen, San Diego, CA, USA) that was visualized by Cy3-conjugated donkey anti-rat secondary antibody (Jackson-Immuno Research Laboratories, West Grove, PA, USA). Samples were mounted with Vectashield mounting medium (Vector Laboratories, Burlingame, CA, USA) and examined by an AxioImager M1 epifluorescence deconvolution microscope with AxioVision 4.8 software (Carl Zeiss AG, Göttingen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The eye lymphatics may serve as a potential target for glaucoma therapy (1187), possibly using a VEGF-C therapy to expand drainage via Schlemm’s canal proposed (41, 523, 845). Anti-angiogenic/lymphangiogenic strategies may prove useful for corneal transplants (1207). In addition, better understanding of the lymphatics of the eye and surrounding orbit may help our with identifying new pharmacologic targets for metastatic disease involving the eye, or autoimmune disease involving the eye such as Graves disease (261).…”
Section: Organization and Anatomy Of The Lymphatic Systemmentioning
confidence: 99%
“…The same study found that TIE2 expression in cervical tumor cells is associated with significantly poor prognosis. Furthermore, treatment with Ang‐2 inhibitors significantly improves outcomes of corneal grafts …”
Section: Current Lymphangiogenesis Researchmentioning
confidence: 99%
“…Furthermore, treatment with Ang-2 inhibitors significantly improves outcomes of corneal grafts. 203 A recent report indicates that fatty acid -oxidation is required for lymphangiogenesis. Lymphangiogenesis is impaired in mice that lack carnitine palmitoyltransferase 1A (CPT1A), a rate-controlling enzyme in fatty acid oxidation.…”
Section: Current Lymphangiogenesis Researchmentioning
confidence: 99%